Mathematical simulation and optimization of cutting mode in turning of workpieces made of nickel-based heat-resistant alloy; Молодежь и современные информационные технологии; Т. 2 - Bogoljubova (Bogolyubova) M. N. Mariya Nikitichna (Информационные технологии в машиностроении, 2016)
Заглавие с титульного экрана